(untitled) (Palíndromo, 2015)
On this paper, we’ll see by means of the analysis of the Sloveninan philoso- pher Slavoj Žižek and the art historian Hal Foster, the importance of thinking the im- brication between subjetivity and culture through psychoanalysis, since the subject from this knowledg instance is made of his or her externality (Other). In its criticism potencial, the psychoanalysis can accom- pany and punctuate the crisis that forms subject and culture, in order to assume a role in both’s continuous changing process. The dialog between arts and psycho- analysis can turn into comprehensible “our time” to resound the unpresent, this is, to make artificial what escapes immediate comprehension , invinting us to a greater reflection. Contemporary art agences critical interventions in culture, inviting to sub- version experiences - and reflection about the subject and the world, mutually cross- ing psychoanalysis and philosophy, among other knowledge areas.